2021
DOI: 10.1007/s12553-020-00517-3
|View full text |Cite
|
Sign up to set email alerts
|

Consultation analysis: use of free text versus coded text

Abstract: General practice in the United Kingdom has been using electronic health records for over two decades, but coding clinical information remains poor. Lack of interest and training are considerable barriers preventing code use levels improvement. Tailored training could be the way forward, to break barriers in the uptake of coding; to do so it is paramount to understand coding use of the particular clinicians, to recognise their needs. It should be possible to easily assess text quantity and quality in medical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Barriers to high quality data include incomplete records, lack of standardisation in data capture systems, technological issues and insufficient resources for ongoing training [ 15 ]. For example, a United Kingdom study that analysed free and coded text (e.g., history, problem, diagnosis, exam, plan codes) in 65 randomly selected general practice consultations found an average of 6% (range 0–13%) of text was entered as coded data and the remainder as free-text [ 11 ]. Furthermore, a study in the United States to validate EMR-derived quality measures found significant undercounting resulting from either incorrectly coded information or information in formats unreadable by automated data methods (i.e., attached letters or reports) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers to high quality data include incomplete records, lack of standardisation in data capture systems, technological issues and insufficient resources for ongoing training [ 15 ]. For example, a United Kingdom study that analysed free and coded text (e.g., history, problem, diagnosis, exam, plan codes) in 65 randomly selected general practice consultations found an average of 6% (range 0–13%) of text was entered as coded data and the remainder as free-text [ 11 ]. Furthermore, a study in the United States to validate EMR-derived quality measures found significant undercounting resulting from either incorrectly coded information or information in formats unreadable by automated data methods (i.e., attached letters or reports) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general practice, secondary use of EMR data can be problematic when clinicians record diagnoses and patient histories as free-text rather than using a diagnosis code from a dropdown list [10][11][12]. Factors that may inhibit the coding of patient diagnoses by clinicians working in Australian general practice include time constraints, lack of sufficient training to correctly code these fields, and insufficient rules or guidelines to direct or enforce coding [11,13]. Hospitals employ clinical coders to correctly code patient records for funding purposes, but this is not the case for general practitioners in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…The primary purpose of EHRs is to help clinicians deliver patient care and most information is entered as unstructured free text, particularly when time is short. 7 High quality data suitable for use in real world studies require structured coding but this is often done by non-clinical staff and coding of evolving symptoms and diagnostic uncertainty is challenging and may be shaped by both unconscious and conscious drivers. 8 Issues with coding poses many problems for research based on EHRs.…”
Section: Introductionmentioning
confidence: 99%
“…Documentation facilitates continuity of care and allows symptoms to be tracked over time 12. Most information is entered into the electronic record as unstructured free text, particularly during time pressed consultations 3. Although free text provides a mostly adequate record of what has taken place in clinical encounters, it is less useful than structured data for NHS management, quality improvement, and research.…”
mentioning
confidence: 99%